Examining the beliefs of non-native English-speaking teachers and EFL students about WCF in enhancing writing skills - Haowei Chen; Ushba Rasool; Ting Hu; Ena Bhattacharyya (Acta Psychologica)
While there has been extensive research on the effectiveness of teacher-written feedback, there is a limited number of studies that have explored the perspectives of feedback practitioners. Specifically, there is a lack of research examining teachers' beliefs about teacher-written feedback, especially when comparing the beliefs of learners from intermediate level. Therefore, there is still a significant amount of knowledge that needs to be acquired on teachers' perceptions of written corrective feedback (WCF) in relation to learners with diverse first languages (L1). In order to address this disparity, a qualitative investigation was undertaken to explore the parallels and distinctions in the beliefs held by EFL students and non-native English-speaking (NNES) educators inside Pakistani university English as a Foreign Language (EFL) context. Thematic analysis was conducted on the in-depth interviews of 6 teachers and 15 students in order to analyze the data. The results of the study indicated that both NNES teachers and EFL learners held various beliefs regarding the four themes of written feedback, namely scope, focus, technique, and orientation. Although they had similar ideas regarding the emphasis placed on feedback, their perspectives diverged in terms of the breadth of feedback coverage. Additionally, the study brought forth several challenges NNES face while teaching. This paper examines the significant consequences that arise in the context of educational practices.